2022
DOI: 10.3389/fgene.2022.914646
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Targets and Potential Mechanisms of Yinchen Wuling San Against Head and Neck Squamous Cell Carcinoma by Network Pharmacology and Molecular Docking

Abstract: Head and neck squamous cell carcinoma (HNSCC) represents one of the most malignant and heterogeneous tumors, and the patients have low 5-year survival. Traditional Chinese medicine (TCM) has been demonstrated as an effective complementary and/or alternative therapy for advanced malignancies including HNSCC. It has been noted that several herbs that are used for preparing Yinchen Wuling San (YWLS) have anti-tumor activities, whereas their mechanisms of action remain elusive. In this study, network pharmacology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…The resulting protein–protein interaction (PPI) network was visualized using Cytoscape software (version 3.9.1). To identify densely connected modules in the network, the molecular complex detection plugin was employed (Zhang et al., 2022). Furthermore, the CytoNCA plugin was used to calculate the node with the highest degree, indicating its importance in the network (Tang et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting protein–protein interaction (PPI) network was visualized using Cytoscape software (version 3.9.1). To identify densely connected modules in the network, the molecular complex detection plugin was employed (Zhang et al., 2022). Furthermore, the CytoNCA plugin was used to calculate the node with the highest degree, indicating its importance in the network (Tang et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In both studies, the PI3K-Akt signaling pathway was recognized as a crucial pathway influenced by bioactive compounds present in these remedies. Moreover, an NP study of Yinchen Wuling San, a complex medical prescription comprising six medicinal plants used for cancer treatment, revealed that the genes TNF, AKT1, and EGFR are targeted by the bioactive compounds of Yinchen Wuling San against HNSCC (Zhang et al, 2022). The gene targets obtained through NP could be further validated through molecular docking and other in silico experiments to confirm the effects of bioactive compounds on these targets.…”
Section: Gene Targets Of Plant Bioactives Against Hncmentioning
confidence: 99%
“…YinchenWuling San (YWLS), comprising of six herbal ingredients, is another potential alternative for HNSCC therapy. However, the active components and antitumor mechanisms of YWLS require further investigation (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%